PENGGUNAAN OUTGUIDE DI UNIT REKAM MEDIS RAWAT JALAN RSUD ARJAWINANGUN KABUPATEN CIREBON - Chynditian; Riantina Luxiarti; Bayu Ajie Pradiptya (Jurnal Kesehatan Mahardika, 2020)
Provision of medical records files quickly and precisely will greatly help the quality of health services provided to patients. If the medical record file storage system that is used is not good, problems will occur that can interfere with the availability of medical record files. Therefore the existence of an outguide in the medical record file storage can help speed up the provision of medical record files and minimize errors in the storage of medical record files. The purpose of this study was to determine the use of outguides in the outpatient medical record unit at Arjawinangun District Hospital Cirebon. This type of research is a descriptive method The subject of this study was the outpatient medical record file storage officer at Arjawinangun District Hospital Cirebon with a total of 4 special officers in the storage and retrieval of medical record files. The instrument used in this study used checklist sheets. The results showed that 100% the use of outguide was not used in the process of searching medical record files because outguide availability was very limited. So when outguide not used properly, it can be errors in the storage of patient's medical record files.For this reason, the medical record unit must use the outguide properly in order to minimize the occurrence of misplacement of the patient's medical record file and speed up the time for the provision of the medical record file.